Characterizing potential subtypes and influencing factors of self-directed learning competence among clinical nurses in China by latent profile analysis - Zhisheng, Zhang; Mingju, Cai; Ruichu, Zhang; Fang, Wang; Shaona, Liao; Anliu, Nie; Xiangfen, Su (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Nurses demonstrate varying levels of self-directed learning competence, which is influenced by multiple individual and contextual factors. Identifying profiles with varying levels of self-directed learning is essential for providing targeted support and training. However, there is limited research exploring the potential profiles of self-directed learning competence among nurses. Objectives: This study aimed to identify distinct latent profiles of self-directed learning competence among nurses and analyze the influencing factors. Methods: A cross-sectional study design was used. Nurses were recruited using a convenience sampling from four tertiary hospitals in Guangzhou, China, between August 2024 and February 2025. The Self-Directed Learning Competence Scale for Nurses was used to assess the self-directed learning Competence of nurses. Latent profile analysis was performed to identify different potential profiles. Pearson’s chi-square test and multinomial logistic regression were used to explore the factors influencing self-directed learning competence. Results: A total of 740 nurses participated. Three latent profiles of self-directed learning competence were identified: low (n = 356, 48.1%), medium (n = 291, 39.3%), and high (n = 93, 12.5%). The self-directed learning competence of nurses was influenced by various factors, including Junior college and below (OR = 0.555, p= 0.043); Monthly number of night shifts = 3 4 (OR = 2.859, p = 0.029); Learning atmosphere = neutral (OR = 0.342, p = 0.018) and good (OR = 0.412, p = 0.038); Learning willingness (OR = 1.425, p <0.001), Difficulty of title promotion = difficult (OR = 2.628, p = 0.029) and Job stress (OR = 0.981, p <0.001). Conclusion: The study revealed diverse profiles of self-directed learning competence among nurses. Nursing managers should design differentiated strategies based on these profiles. Enhancing organizational support and stimulating learning motivation can help improve nurses’ self-directed learning competence, thereby promoting their professional development and improving the overall quality of clinical nursing care.